Socialización: ¿familia vs escuela? - Guevara Granados, Vicky (2011)
The main task of schools and families is to train and educate children, a common task wh ich should guarantee by itself a clase cooperation and mutual help. Nevertheless instead of using its resources as a whole to salve child problems with success, a deteriorated relationship between both parties is presented as a scene in which every party acts as it considers t he best for the child, undermining the authority and effectiveness ofthe other pa rty.